Legal Analysis of the Rights of Pregnant or Maternity Women Workers in Indonesia - Amaliyah, Vivi (Jurnal Legisci, 2023)
Every company certainly needs employees as personnel who carry out every activity in the company organization. Normative labor rights are often ignored by companies, for example, there are labor wages that are still below the Provincial Minimum Wage (UMP), inappropriate workplace facilities, not providing work leave, and employing women, especially pregnant women without paying attention to and protecting decency and security while at work. Many are found in some employment contracts in some companies that require women to voluntarily resign when the woman becomes pregnant. The research method in this thesis is carried out with normative juridical research. Collection of legal materials in the form of primary and secondary materials in the form of literature studies, observations, questionnaires, and interviews. The analysis carried out is qualitative. The results show that the rights of female employees have been fully fulfilled, it's just that there are some shortcomings such as breastfeeding room facilities are still lacking.